Improvement of primary school students’ activeness and outcome using discovery learning model in mathematics - Pingky Fitriany Pasaribu; Firosalia Kristin; Indri Anugraheni (Jurnal Pendidikan dan Pengajaran, 2019)
This study aims to determine the increase in activity and learning outcomes of 5th grade students of SD Negeri Randuacir 02 Salatiga Semester II Year 2018/2019 using the discovery learning model. This type of research is classroom action research (CAR). The research subjects were 29 students in grade 5. Procedure for classroom action research in the form of planning, implementation, observation and reflection. The action was carried out in two cycles with each cycle of three meetings. Data collection techniques in this study used observation and tests. The data analysis technique is done by using descriptive comparative analysis in the form of a percentage comparison in the initial conditions before the action is taken, the results of the first cycle, and the results of the second cycle. The results showed an increase in the activeness and learning outcomes of mathematics through the implementation of the discovery learning model. This is evidenced in the rubric of the activity of the first cycle, the average value is 29.66, the criteria are quite good, increasing in the second cycle with the average score being 45.03 criteria very good. The learning outcomes with the KKM provisions are 70, in the pre-cycle only 17.24% were completed, in the first cycle it increased to 55.18%, and in the second cycle the action increased to 72.41%.